A multi‐length‐scale USAXS/SAXS facility: 10–50 keV small‐angle X‐ray scattering instrument. (25th September 2013) - Freelon, Byron; Suthar, Kamlesh; Ilavsky, Jan
Abstract : Coupling small‐angle X‐ray scattering (SAXS) and ultra‐small‐angle X‐ray scattering (USAXS) provides a powerful system of techniques for determining the structural organization of nanostructured materials that exhibit a wide range of characteristic length scales. A new facility that combines high‐energy (HE) SAXS and USAXS has been developed at the Advanced Photon Source (APS). The application of X‐rays across a range of energies, from 10 to 50 keV, offers opportunities to probe structural behavior at the nano‐ and microscale. An X‐ray setup that can characterize both soft matter or hard matter and high‐ Z samples in the solid or solution forms is described. Recent upgrades to the Sector 15ID beamline allow an extension of the X‐ray energy range and improved beam intensity. The function and performance of the dedicated USAXS/HE‐SAXS ChemMatCARS‐APS facility is described.